Development of An Examination Authentication Embedded System Based on Fingerprint Approach - Oyedepo (Member IAENG), Oyediran Mayowa; Bolanle, Wahab Wajeed; Wasiat, Elegbede Adedayo; Jolie, Enegbe Toye (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2018)
Security is crucial all around. Access into institutions, examination centers, organizations or even estates ought to be controlled and closely monitored through a verification system. The method of authenticating a student for an examination has an obvious problem such as presentation of fake clearance card, impersonation and so on and the unethical manner associated with the examination is a grim issue that requires the stakeholders in academic area to seek for alternative means of authenticating student for examination, because the manual paper-based clearance process is fundamentally flawed. Sequel to that, a dependable and effective system is designed to tackle the issues of the convectional technique. The system will verify the understudy using fingerprint biometrics technique and generate a report which can serve as an attendance.